Die grosse Edgar Wallace Krimi-Collection - Wallace, Edgar 1875-1932; Wallace, Edgar 1875-1932 (Pidax Film- und Hörspielverlag, 2024)
A CID detective is lured into a plot by girl who first pretends to fall in love with him, then that she's been killed and is now actually a heretofore unknown twin sister, and ultimately a murderous betrayal. [www.imdb.de]
Fernsehfilm. Großbritannien. 1963
Keywords: Fernsehserie; DVD-Video